IMPROVING POST STROKE FUNCTIONAL ABILITY USING THE BOBATH CONCEPT: A CASE REPORT - Handoko, Topan; Susilo, Taufik Eko; Fauziah, Maulida R. (Universitas Muhammadiyah Surakarta, 2021)
Introduction: Stroke is one of the health problems that causes disability. According to the World Stroke Health Organization, there are 13.7 million new cases of stroke that cause a decrease in functional ability every year. Physiotherapy interventions based on the Bobath Concept are one of the interventions that are widely used to treat disability problems in post-stroke patients, although the results of these interventions may vary. A study is needed in the management of handling disability in post-stroke using the Bobath Concept, in order to improve functional abilities. This aim can be achieved through exercises that refer to postural improvement, movement analysis, selective movement and the role of sensory information to achieve functional targets. Case Presentation: A 65-year-old man was diagnosed with a right ischemic stroke in December 2020 with a condition of hemiparesis on his left side of the body, 1 week after that the patient was referred for physiotherapy at the Halmahera Medika Main Clinic. The patient reported having hypercholesterolemia. During the initial stroke, the patient feels a cold and limp sensation on the side of the lesion. The results of the examination showed that the patient had impaired postural control, decreased selective movement ability, which led to a decrease in functional ability. Management and Outcome: Patients undergo a therapy program every 3 times a week and each session lasts 40-50 minutes. Physiotherapy with the Bobath concept includes facilitation to activate postural muscles and to suppress the synergistic pattern of stroke, pelvic mobilization, hip mobilization, active assisted exercise, positioning how to sleep to sitting, balance and coordination exercises, walking exercises and facilitation of weight bearing. At the end of the study the patient experienced an increase in functional ability,especially transfer and walking catagory. From the results we can state that there is an increase in the patient's functional status based on the Barthel Index, especially in the ability to transfer and walk on a flat road. Discussion: Two articles have been selected to support and compare with this study, the findings of which are in line with the research of Besios et al (2019), and Mikołajewska (2013). Base on the functional movement analysis and response to facilitation, which is part of the assessment, it shows that the given exercises improve postural orientation and posture stabilization in sitting, standing, and walking. This is the reason how the functional abilities in our patients developed after the intervention especially the transfer and ambulation abilities of walking. Conclusion: The conclusion of this case report is that there is an increase in functional ability, especially the patient's ability to transfer or ambulate independently on one of the Barthel index items, several other items also experienced an increase although not as much as an increase in transfer ambulation.